INNOVATION ENCOURAGING ENVIRONMENTAL LEARNING MANAGEMENT FOR PRIMARY SCHOOL STUDENTS UNDER BANGKOK METROPOLITAN ADMINISTRATION - Parijãno (Chatku), PhrakrupaladSupachai; (Udomsak Uttamasakko), PhrakhruWirunsutakhun; Boonpoo, Somsak (Journal of Educational Review Faculty of Education in MCU, 2020)
This research paper aimed to propose innovation encouraging environmental learning management for primary school students under Bangkok Metropolitan Administration. Mixed methods research was designed and was divided into 3 steps. Step 1: Study environment learning management. The questionnaire was used by 390 administrators and teachers, and data were analyzed by using descriptive statistics consisted of frequency, percentage, mean and standard deviation. Step 2: develop innovation by interviewing 24 key informants with interview form, and data was analyzed by content analysis. Step 3: propose innovation encouraging environmental learning management by focus group discussion of 10 experts with questions for focus group discussion, and data was analyzed by content analysis. Research results found that innovation encouraging environmental learning management for primary school students under Bangkok Metropolitan Administration consisted of 4 components: 1) principles, 2) purpose, 3) operational methods, and 4) process. It was an action to develop educational innovations that encouraged learning management. These learning management innovations can emphasize the process of learning management within educational institutions in 5 areas: (1) innovation in teaching and learning, (2) innovation in teaching and learning methods, (3) innovation in curriculum, (4) measurement and evaluation Innovation, (5) management innovation by integrating with the environment that encouraged innovation in learning management in 3 areas which were physical within the school, society within the school, and teaching and instruction.